Model dan Kendali Modular pada Pendulum Terbalik tipe Rotary - Erwin Susanto (Jurnal Rekayasa Elektrika, 2023)
Rotary Inverted Pendulum (RIP) is a physical system that is often used as a theoretical platform and application of non-linear, unstable, and underactuated control systems so that it poses a challenge to design controls and realize them. The mechanical construction of the system consists of a pendulum arm that rotates horizontally on the RIP base shaft and a vertical pendulum arm that swings from a downward position to an upright equilibrium position. This paper presents a model and control scheme for RIP in a modular manner, in which three controller sections are constructed and realized using Multibody Matlab. The three controller parts include: a swing-up using a positive feedback Proportional Derivative controller, a switching mode controller that works to change swing up control scheme into stabilization control when the vertical pendulum arm reaches a position around its upright equilibrium, and stabilization controller to maintain vertical arm balanced using a Proportional Derivative controller. The trajectory of the motion of the pendulum arm and the 3D visualization of the pendulum system presented using Multibody Matlab show the effectiveness of the applied method.